A production process of a nano tungsten carbide reinforced iron-nickel base valve seat

CN122918562APending Publication Date: 2026-10-16JIANGHAN OILFIELD HONGJIA MACHINERY QIANJIANG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611156753.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]上述技术方案中,所用组分均为独立的单一粉体原料,各功能元素以离散形式存在,即便完成粉体混合,各改性组分也难以与纳米碳化钨形成稳定的界面结合结构,导致材料表面硬度提升效果有限,当该类材料应用于泥浆泵凡尔座这类承受高频冲击与含砂介质冲蚀的严苛工况时,界面区域易产生应力集中,使得材料的磨损更加严重,无法满足凡尔座长效稳定服役的使用要求

Benefits of technology

1、本发明在纳米碳化钨增强的铁镍基合金凡尔座的生产工艺中,采用溶胶-凝胶法构建铈-钛-钼络合体系,其中,铈元素作为稀土元素可发挥晶粒细化与熔池净化作用,钛元素能够提升材料在高温下的结构稳定性,构建稳定的氧化物骨架,钼元素可改善体系润湿性能并优化减摩效果,经空气氛围热解处理后,形成的铈-钛-钼复合氧化物相,实现改性组分的均匀分布,为提升凡尔座熔覆层均匀性与表面硬度奠定基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918562A_ABST
    Figure CN122918562A_ABST
Patent Text Reader

Abstract

The application discloses a production process of a nano-carbide tungsten reinforced iron-nickel-based alloy valve seat and belongs to the technical field of valve seat production. The production process comprises the following steps: firstly, a cerium-titanium-molybdenum complex dry gel is prepared through a sol-gel method, and a cerium-titanium-molybdenum composite oxide powder is obtained after calcination in an air atmosphere; secondly, iron-nickel-based alloy powder, nano-carbide tungsten and the cerium-titanium-molybdenum composite oxide powder are ball-mixed to prepare nano-carbide tungsten reinforced iron-nickel-based composite alloy powder; finally, a cladding layer is prepared on the surface of a sandblasted and cleaned valve seat substrate by adopting a laser cladding process, so as to obtain the nano-carbide tungsten reinforced iron-nickel-based alloy valve seat. Through the interface modification effect of the cerium-titanium-molybdenum composite oxide powder, the uniform distribution of the alloy powder is realized, the interface bonding performance of the reinforced phase and the substrate is effectively improved, the wear resistance of the valve seat is improved, and the service stability of the valve seat under the load working conditions of sand slurry erosion and high-frequency impact is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of valve manufacturing technology, specifically a manufacturing process for a nano-tungsten carbide-reinforced iron-nickel-based alloy valve. Background Technology

[0002] Mud pumps are core hydraulic equipment in oil drilling systems. The valve seat, as its core sealing and pressure-bearing component, operates under long-term erosion, friction, and high-pressure alternating loads from sand-containing mud, making it highly susceptible to wear and spalling, leading to seal failure. While traditional alloy steel valve seats offer good strength and toughness, their surface hardness and wear resistance are limited, making them unsuitable for long-term, harsh operating conditions.

[0003] Tungsten carbide is characterized by high hardness and excellent wear resistance, making it the most commonly used hard reinforcing phase for improving the wear resistance of metallic materials. It is widely used in the strengthening and modification of various heavy-duty wear-resistant components. In the existing technical solutions, Chinese patent application with publication number CN120700344A discloses a high-wear-resistant tungsten carbide alloy and its preparation method. Hard particles are prepared by mixing tungsten carbide with nano carbon black, titanium powder, zirconium powder and rare earth oxides. Then, tungsten carbide, molybdenum carbide, alumina, rare earth oxides and cobalt powder and copper powder are ball-milled and mixed to obtain the matrix raw material. The hard particles are added to the matrix raw material and ball-milled and mixed again. The mixture is then plasma sintered to obtain the final product.

[0004] In the above technical solutions, all components are independent single powder raw materials, and each functional element exists in a discrete form. Even if the powder is mixed, it is difficult for each modified component to form a stable interfacial bonding structure with nano-tungsten carbide, resulting in a limited effect on improving the surface hardness of the material. When this type of material is applied to harsh working conditions such as mud pump valve seats that are subjected to high-frequency impact and sand-containing media erosion, stress concentration is easily generated in the interfacial area, making the wear of the material more serious and failing to meet the requirements for long-term stable service of the valve seat. Summary of the Invention

[0005] The purpose of this invention is to provide a production process for a nano-tungsten carbide-reinforced iron-nickel-based alloy valve seat. Cerium-titanium-molybdenum composite oxide powder is used as an interface modifier to jointly construct a reinforcing phase alloy system with nano-tungsten carbide and iron-nickel-based alloy. The functional layer is formed on the surface of the valve seat by laser cladding, which meets the requirements for long-term stable service of the valve seat under harsh working conditions.

[0006] The objective of this invention can be achieved through the following technical solutions: This invention provides a manufacturing process for a nano-tungsten carbide-reinforced iron-nickel-based alloy valve, comprising the following steps: Step 1: Using an alloy steel valve seat as the substrate, the working surface to be clad is pretreated by sandblasting and cleaning, and then dried to obtain the valve seat substrate to be clad. Step 2: Fix the valve base to be clad onto the CNC laser processing table, and use a laser coaxial feeding method to laser cladize the valve base to be clad onto the substrate. After annealing and grinding and polishing, a nano-tungsten carbide reinforced iron-nickel-based alloy valve base is obtained.

[0007] The laser power for laser cladding is 1200-2000W, and the scanning speed is 4-8mm / s.

[0008] The specific process of laser coaxial powder feeding is as follows: Nano-tungsten carbide reinforced iron-nickel-based composite alloy powder is loaded into a powder feeder, and argon gas is used as a protective carrier gas to deliver it to a coaxial nozzle for ejection. The powder then converges at the laser focal point to form a stable powder flow, and the powder feeding rate is controlled at 15-30 g / min.

[0009] Furthermore, the tungsten carbide nano-reinforced iron-nickel-based composite alloy powder was obtained by ball milling iron-nickel-based alloy powder, tungsten carbide nano-powder, and cerium-titanium-molybdenum composite oxide powder under the conditions of anhydrous ethanol as the dispersion medium and argon as the protective atmosphere.

[0010] The ball-to-material ratio for ball milling is 6:1-8:1, and the ball milling time is 3-5 hours.

[0011] The mass ratio of iron-nickel-based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder is 60-80:10-20:1.

[0012] Furthermore, the cerium-titanium-molybdenum composite oxide powder is obtained by calcining the cerium-titanium-molybdenum complex dry gel in an air atmosphere.

[0013] The high-temperature calcination temperature is 500-550℃, the heating rate is 8℃ / min, and the time is 40-60min.

[0014] Furthermore, the cerium-titanium-molybdenum complex dry gel was prepared by a sol-gel method using tetrabutyl titanate ethanol solution as the titanium-based main framework and cerium nitrate hexahydrate and ammonium molybdate as active coordinating metals, in a solvent system of anhydrous ethanol and deionized water and with the synergistic chelation of acetylacetone and glacial acetic acid.

[0015] The tetrabutyl titanate ethanol solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol at a volume ratio of 1:3.

[0016] The temperature for sol-gel is 25-35℃.

[0017] The beneficial effects of this invention are: 1. In the production process of nano-tungsten carbide reinforced iron-nickel based alloy valve seats, the present invention adopts the sol-gel method to construct a cerium-titanium-molybdenum complex system. Cerium, as a rare earth element, can play a role in grain refinement and molten pool purification. Titanium can improve the structural stability of the material at high temperature and construct a stable oxide skeleton. Molybdenum can improve the wettability of the system and optimize the friction reduction effect. After pyrolysis treatment in an air atmosphere, the cerium-titanium-molybdenum composite oxide phase is formed, which realizes the uniform distribution of modified components and lays the foundation for improving the uniformity and surface hardness of the valve seat cladding layer.

[0018] 2. In the production process of the tungsten carbide-reinforced iron-nickel alloy valve seat, this invention introduces cerium-titanium-molybdenum composite oxide powder as an interface modifier. This powder is ball-milled with tungsten carbide and iron-nickel alloy powders. During the high-energy impact of the ball milling process, the composite oxide powder, with its active surface, plays a role in physical diffusion and microscopic modification between the powder interfaces. This ensures that the tungsten carbide is uniformly dispersed in the iron-nickel alloy powder. In the subsequent laser cladding process, the uniformly dispersed interface environment helps reduce the interfacial tension between the liquid metal and the hard phase, enhancing the anchoring force of the tungsten carbide in the alloy matrix, improving the erosion and wear resistance of the cladding layer, and mitigating the problem of easy wear and failure of the valve seat under high-frequency impact conditions, thus extending its stable service life. Attached Figure Description

[0019] Figure 1 This is an SEM image of the laser cladding surface of the nano-tungsten carbide-reinforced iron-nickel-based alloy valve prepared in Example 2 of the present invention.

[0020] Figure 2 The image shows an SEM image of the laser cladding surface of the nano-tungsten carbide reinforced iron-nickel based alloy valve prepared in Example 2 of this invention after wear resistance testing. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1: This example provides a manufacturing process for a nano-tungsten carbide-reinforced iron-nickel-based alloy valve seat, including the following steps: S1: 2g of cerium nitrate hexahydrate, 5g of ammonium molybdate, 30mL of acetylacetone, 100mL of anhydrous ethanol and 1mL of deionized water were placed in a reaction vessel. Glacial acetic acid was added to adjust the pH of the reaction to 3.8. The mixture was stirred at 200r / min for 20min at 25℃. 400mL of tetrabutyl titanate ethanol solution (prepared by mixing tetrabutyl titanate and anhydrous ethanol in a volume ratio of 1:3) was slowly added to the reaction vessel. The reaction was continued for 2h at the same temperature and stirring rate. After the reaction was completed, the mixture was aged for 8h and dried under vacuum at 60℃ to constant weight to obtain cerium-titanium-molybdenum complex dry gel.

[0023] This step utilizes a sol-gel method to achieve uniform composite formation of cerium, titanium, and molybdenum. Tetrabutyl titanate is used as the titanium source precursor, and acetylacetone is introduced as a chelating agent to form a stable chelate structure with titanium ions, effectively controlling the hydrolysis rate of the titanium source. In a weakly acidic system regulated by glacial acetic acid, the metal ions dissociated from cerium nitrate hexahydrate and ammonium molybdate undergo a co-condensation reaction with the titanium hydroxyl groups generated from the hydrolysis of the titanium source, constructing a complex network structure with titanium-oxygen bonds as the backbone, thus obtaining a cerium-titanium-molybdenum complex dry gel.

[0024] S2: Grind 60g of cerium-titanium-molybdenum complex dry gel and place it in a ceramic crucible. Then place it in a tube furnace under air atmosphere and heat it to 500℃ at a heating rate of 8℃ / min. Hold the temperature for 40min. After the reaction is completed, cool it to room temperature, grind it and sieve it through a 200-mesh sieve to obtain cerium-titanium-molybdenum composite oxide powder.

[0025] This step involves the pyrolysis, oxidation, and solid-phase transformation of the cerium-titanium-molybdenum complex dry gel via air calcination. In an air atmosphere, the organic chelating groups and volatile solvents within the dry gel decompose and evaporate, eliminating carbon impurities in the system. The original complex network framework undergoes solid-phase recombination, and cerium, titanium, and molybdenum polymetallic ions simultaneously complete the oxidation reaction, yielding cerium-titanium-molybdenum composite oxide powder.

[0026] S3: Iron-nickel based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder were placed in a planetary ball mill (the mass ratio of iron-nickel based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder was 60:10:1). Anhydrous ethanol was added as the dispersion medium, and argon gas was introduced as the protective atmosphere. The ball-to-material ratio was controlled at 6:1. The mixture was ball-milled at 200 r / min for 3 h. After mixing, the mixture was vacuum dried at 60 °C for 2 h. The powder was then sieved through a 200-mesh sieve to obtain nano-tungsten carbide reinforced iron-nickel based composite alloy powder.

[0027] This step employs an argon-protected wet ball milling process to achieve uniform compounding and mechanical activation of multi-component powders. Using anhydrous ethanol as the dispersion medium, the shearing and impact forces of a planetary ball mill are utilized to achieve uniform mixing of iron-nickel-based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder. Simultaneously, the cerium-titanium-molybdenum composite oxide powder acts as an interface modifier, optimizing the interfacial contact state of each phase, thus obtaining nano-tungsten carbide-reinforced iron-nickel-based composite alloy powder.

[0028] S4: The 42CrMo alloy steel valve seat, forged and machined to the design size, is used as the base. The working surface to be clad is sandblasted using a sandblasting machine. Then, the base is placed in an ultrasonic cleaner and cleaned with anhydrous ethanol for 15 minutes to remove surface oil and dust impurities. After being taken out, it is placed in a forced-air drying oven and dried at a constant temperature of 70°C for 20 minutes. After natural cooling, the valve seat base to be clad is obtained.

[0029] S5: Fix the valve base to be clad onto the CNC laser processing table, load nano-tungsten carbide reinforced iron-nickel-based composite alloy powder into the powder feeder, and use laser coaxial powder feeding method, with argon gas as the powder carrier gas to deliver the powder to the coaxial nozzle for ejection, and gather at the laser focus to form a stable powder flow, and perform laser cladding on the working surface of the valve base under the protection of argon gas, controlling the laser power to be 1200W, the scanning speed to be 4mm / s, and the powder feeding rate to be 15g / min. After cladding, transfer the workpiece to a pit-type tempering furnace for stress relief annealing, heat to 500℃ at 5℃ / min, hold for 2h, and then cool to room temperature with the furnace, grind and polish to obtain nano-tungsten carbide reinforced iron-nickel-based alloy valve base.

[0030] Example 2: This example provides a manufacturing process for a nano-tungsten carbide-reinforced iron-nickel-based alloy valve seat, including the following steps: S1: 5g of cerium nitrate hexahydrate, 10g of ammonium molybdate, 45mL of acetylacetone, 150mL of anhydrous ethanol and 1.5mL of deionized water were placed in a reaction vessel. Glacial acetic acid was added to adjust the pH of the reaction to 4. The mixture was stirred at 250r / min for 30min at 30℃. 600mL of tetrabutyl titanate ethanol solution (prepared by mixing tetrabutyl titanate and anhydrous ethanol in a volume ratio of 1:3) was slowly added to the reaction vessel. The reaction was continued for 3h at the same temperature and stirring rate. After the reaction was completed, the mixture was aged for 10h and dried under vacuum at 70℃ to constant weight to obtain cerium-titanium-molybdenum complex dry gel.

[0031] S2: 90g of cerium-titanium-molybdenum complex dry gel was ground and placed in a ceramic crucible and placed in a tube furnace under air atmosphere. The temperature was increased to 525℃ at a heating rate of 8℃ / min and held for 50min. After the reaction was completed, it was cooled to room temperature, ground and sieved through a 250-mesh sieve to obtain cerium-titanium-molybdenum composite oxide powder.

[0032] S3: Iron-nickel based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder were placed in a planetary ball mill (the mass ratio of iron-nickel based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder was 70:15:1). Anhydrous ethanol was added as the dispersion medium, and argon gas was introduced as the protective atmosphere. The ball-to-material ratio was controlled at 7:1. The mixture was ball-milled at 250 r / min for 4 h. After mixing, the mixture was vacuum dried at 75 °C for 3 h. The powder was then sieved through a 250 mesh sieve to obtain nano-tungsten carbide reinforced iron-nickel based composite alloy powder.

[0033] S4: The 42CrMo alloy steel valve seat, forged and machined to the design size, is used as the base. The working surface to be clad is sandblasted using a sandblasting machine. Then, the base is placed in an ultrasonic cleaner and cleaned with anhydrous ethanol for 18 minutes to remove surface oil and dust impurities. After being taken out, it is placed in a forced-air drying oven and dried at a constant temperature of 80°C for 30 minutes. After natural cooling, the valve seat base to be clad is obtained.

[0034] S5: Fix the valve base to be clad onto the CNC laser processing table, load nano-tungsten carbide reinforced iron-nickel-based composite alloy powder into the powder feeder, and use laser coaxial powder feeding method, with argon gas as the powder carrier gas to deliver the powder to the coaxial nozzle for ejection, and gather at the laser focus to form a stable powder flow, and perform laser cladding on the working surface of the valve base under the protection of argon gas, controlling the laser power to be 1600W, the scanning speed to be 6mm / s, and the powder feeding rate to be 22g / min. After cladding, transfer the workpiece to a pit-type tempering furnace for stress relief annealing, heating to 525℃ at 5℃ / min, holding for 3h, and then cooling to room temperature with the furnace, grinding and polishing to obtain nano-tungsten carbide reinforced iron-nickel-based alloy valve base.

[0035] Example 3: This example provides a manufacturing process for a nano-tungsten carbide-reinforced iron-nickel-based alloy valve seat, including the following steps: S1: 8g of cerium nitrate hexahydrate, 15g of ammonium molybdate, 60mL of acetylacetone, 200mL of anhydrous ethanol and 2mL of deionized water were placed in a reaction vessel. Glacial acetic acid was added to adjust the pH of the reaction to 4.2. The mixture was stirred at 300r / min for 40min at 35℃. 800mL of tetrabutyl titanate ethanol solution (prepared by mixing tetrabutyl titanate and anhydrous ethanol in a volume ratio of 1:3) was slowly added to the reaction vessel. The reaction was continued for 4h at the same temperature and stirring rate. After the reaction was completed, the mixture was aged for 12h and dried under vacuum at 80℃ to constant weight to obtain cerium-titanium-molybdenum complex dry gel.

[0036] S2: 120g of cerium-titanium-molybdenum complex dry gel was ground and placed in a ceramic crucible and placed in a tube furnace under air atmosphere. The temperature was increased to 550℃ at a heating rate of 8℃ / min and held for 60min. After the reaction was completed, it was cooled to room temperature, ground and sieved through a 300-mesh sieve to obtain cerium-titanium-molybdenum composite oxide powder.

[0037] S3: Iron-nickel-based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder were placed in a planetary ball mill (the mass ratio of iron-nickel-based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder was 80:20:1). Anhydrous ethanol was added as the dispersion medium, and argon gas was introduced as the protective atmosphere. The ball-to-material ratio was controlled at 8:1. The mixture was ball-milled at 300 r / min for 5 h. After mixing, the mixture was vacuum dried at 90 °C for 4 h. The powder was then sieved through a 300-mesh sieve to obtain nano-tungsten carbide-reinforced iron-nickel-based composite alloy powder.

[0038] S4: The 42CrMo alloy steel valve seat, forged and machined to the design size, is used as the base. The working surface to be clad is sandblasted using a sandblasting machine. Then, the base is placed in an ultrasonic cleaner and cleaned with anhydrous ethanol for 20 minutes to remove surface oil and dust impurities. After being taken out, it is placed in a forced-air drying oven and dried at a constant temperature of 90℃ for 40 minutes. After natural cooling, the valve seat base to be clad is obtained.

[0039] S5: Fix the valve base to be clad onto the CNC laser processing table, load nano-tungsten carbide reinforced iron-nickel-based composite alloy powder into the powder feeder, and use laser coaxial powder feeding method, with argon gas as the powder carrier gas to deliver the powder to the coaxial nozzle for ejection, and gather at the laser focus to form a stable powder flow, and perform laser cladding on the working surface of the valve base under the protection of argon gas, controlling the laser power to be 2000W, the scanning speed to be 8mm / s, and the powder feeding rate to be 30g / min. After cladding, transfer the workpiece to a pit-type tempering furnace for stress relief annealing, heating to 550℃ at 5℃ / min, holding at 4h, and then cooling to room temperature with the furnace, grinding and polishing to obtain nano-tungsten carbide reinforced iron-nickel-based alloy valve base.

[0040] The thickness of the laser cladding surface in Examples 1-3 above is 1.5 mm. Comparative Example 1: The difference from Example 2 is that the cerium nitrate hexahydrate added in step S1 is removed, while the other steps remain unchanged. A composite alloy powder is prepared and then a nano-tungsten carbide-reinforced iron-nickel-based alloy valve is obtained by laser cladding process.

[0041] Comparative Example 2: The difference from Example 2 is that the addition of ammonium molybdate in step S1 is removed, while the other steps remain unchanged. Composite alloy powder is prepared and then processed into nano-tungsten carbide reinforced iron-nickel based alloy valves by laser cladding process.

[0042] Comparative Example 3: The difference from Example 2 is that in step S3, the mass ratio of iron-nickel-based alloy powder, nano-tungsten carbide and cerium-titanium-molybdenum composite oxide powder is 75:15:0.5, while the other steps remain unchanged. Composite alloy powder is prepared and nano-tungsten carbide-reinforced iron-nickel-based alloy valve seat is obtained by laser cladding process.

[0043] Comparative Example 4: The difference from Example 2 is that in step S3, the mass ratio of iron-nickel-based alloy powder, nano-tungsten carbide and cerium-titanium-molybdenum composite oxide powder is 75:15:1.5, while the other steps remain unchanged. Composite alloy powder is prepared and nano-tungsten carbide-reinforced iron-nickel-based alloy valve seat is obtained by laser cladding process.

[0044] Comparative Example 5: The difference from Example 2 is that the cerium-titanium-molybdenum composite oxide powder prepared in step S2 is removed in step S3, while the other steps remain unchanged, and a composite alloy powder is prepared. The powder is then processed by laser cladding to obtain a nano-tungsten carbide-reinforced iron-nickel-based alloy valve seat.

[0045] The iron-nickel based alloy powder purchased in the above embodiments and comparative examples was produced by Jiangsu Boqian New Material Co., Ltd., with the grade NiFe50-GB150; the nano-tungsten carbide was produced by Shanghai Liantian Material Technology Co., Ltd., with the product number LT-C-005-1 and an average particle size of 100nm.

[0046] The nano-tungsten carbide-reinforced iron-nickel-based alloy valves prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to performance tests, and the test results are shown in Table 1. Sample preparation: The nano-tungsten carbide reinforced iron-nickel based alloy valves prepared in each example and comparative example were made into samples according to the standards and requirements of each test.

[0047] Hardness performance: Refer to standard GB / T 4340.1-2009 "Metallic materials Vickers hardness test - Part 1: Test method" and use a Vickers hardness tester to test the hardness. Measure five points randomly selected on the sample surface and take the average value. The higher the hardness value, the better the hardness performance of the material.

[0048] Wear resistance performance: Simulating the actual service conditions of a mud pump, the test was conducted using a liquid erosion wear testing machine. The sample was fixed, and a sand-containing mud slurry (composed of 1000 mL water, 150 g quartz sand, and 50 g bentonite) was used as the erosion medium. The erosion angle was set at 45°, the erosion pressure at 0.6 MPa, and the erosion was carried out continuously for 4 hours. After the test, the mass of the sample before and after erosion was measured, and the wear rate was calculated. The lower the wear rate, the better the wear resistance of the material.

[0049] Table 1. Performance Test Table of Nano-Tungsten Carbide Reinforced Iron-Nickel Based Alloy Valve Hardness value 862 885 908 815 828 798 845 732 Wear rate (mg / h) 0.28 0.22 0.18 0.55 0.68 0.75 0.42 1.35 As shown in Table 1, the hardness and wear resistance of the nano-tungsten carbide-reinforced iron-nickel-based alloy valves prepared in Examples 1-3 are significantly better than those in the comparative examples. This indicates that the present invention constructs a cerium-titanium-molybdenum composite oxide by means of a sol-gel method and uses it as an interface modifier to ball-mill with nano-tungsten carbide and iron-nickel-based alloy powder to form a uniformly dispersed composite alloy powder. This process layout may effectively improve the wettability between the hard phase and the matrix and construct a strong and tough interfacial bonding structure, thereby significantly improving the structural stability and wear resistance of the valve in the erosion environment of sandy mud.

[0050] The hardness and wear resistance of the sample in Comparative Example 1 showed a significant decrease, possibly because the cerium component was missing from the system, thus losing the purification and valence regulation effects of rare earth elements on the laser molten pool. The lack of cerium may lead to coarsening of the cladding layer grains and an inability to effectively capture impurities in the molten pool, making it easy for microcracks to initiate at the grain boundaries when the material is subjected to high-frequency erosion, resulting in a weakening of the overall erosion resistance.

[0051] The wear rate of the sample in Comparative Example 2 increased significantly, and the hardness also decreased. This may be because the lack of molybdenum in the system caused the composite oxide to lose its crucial wetting regulation ability and self-lubricating potential. During the high-temperature process of laser cladding, the lack of molybdenum element regulation may increase the contact angle between the liquid metal matrix and nano-tungsten carbide, resulting in poor interfacial wettability. The hard phase exists in the matrix only in a weak mechanical interlocking form, leading to a significant reduction in the wear life of the material.

[0052] The limited improvement in various properties of the sample in Comparative Example 3 may be due to the low addition amount of cerium-titanium-molybdenum composite oxide powder, which fails to form a continuous and effective active transition layer on the surface of nano-tungsten carbide during ball milling, resulting in insufficient interface modification and failure to fully exert its anchoring effect on the reinforcing phase.

[0053] Although the hardness of the standard sample in Comparative Example 4 remained at a high level, its wear rate actually increased compared to Example 2. This may be because the amount of cerium-titanium-molybdenum composite oxide powder added was too high, causing the excess oxide to segregate at the grain boundaries, which may introduce more brittle phases or inclusions into the cladding layer. Under erosion impact, these brittle areas are prone to become stress concentration points and induce micro-scraping, which in turn impairs the overall wear resistance of the material.

[0054] The standard sample in Comparative Example 5 exhibited the lowest hardness and the highest wear rate, further demonstrating that the cerium-titanium-molybdenum composite oxide prepared in this invention achieves pre-modification of the interface of nano-tungsten carbide. This composite oxide, likely through the combined action of ball milling and laser cladding, may have resulted in strong interfacial bridging and chemisorption between the hard phase and the metal matrix, ensuring the long-term stability of the valve seat under harsh operating conditions.

[0055] Depend on Figure 1 and Figure 2 It can be seen that the nano-tungsten carbide reinforced iron-nickel based alloy cladding layer prepared in Example 2 of the present invention has no obvious pores and cracks. The nano-tungsten carbide particles are uniformly distributed in the matrix without obvious agglomeration and segregation, indicating that the cerium-titanium-molybdenum composite oxide may have an interface modification and dispersion control effect during ball milling and cladding. After erosion and wear test, the surface of the cladding layer only shows a slightly uniform erosion morphology, without obvious peeling and interface cracking, indicating that the nano-tungsten carbide reinforced iron-nickel based alloy valve prepared in the present invention has good erosion and wear resistance, which is consistent with the hardness and wear rate test results, and improves the service reliability of the valve.

[0056] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A manufacturing process for a nano-tungsten carbide-reinforced iron-nickel-based alloy valve, characterized in that, Includes the following steps: Step 1: Using an alloy steel valve seat as the substrate, the working surface to be clad is pretreated by sandblasting and cleaning, and then dried to obtain the valve seat substrate to be clad. Step 2: Fix the valve base to be clad onto the CNC laser processing table, and use a laser coaxial feeding method to laser cladize the valve base to be clad onto the substrate. After annealing and grinding and polishing, a nano-tungsten carbide reinforced iron-nickel-based alloy valve base is obtained.

2. The production process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 1, characterized in that, The laser power of the laser cladding is 1200-2000W, and the scanning speed is 4-8mm / s.

3. The production process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 1, characterized in that, The specific process of laser coaxial powder delivery is as follows: Nano-tungsten carbide reinforced iron-nickel-based composite alloy powder is loaded into a powder feeder, and argon gas is used as a protective carrier gas to deliver it to a coaxial nozzle for ejection. The powder then converges at the laser focal point to form a stable powder flow, and the powder feeding rate is controlled at 15-30 g / min.

4. The manufacturing process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 1, characterized in that, The nano-tungsten carbide reinforced iron-nickel-based composite alloy powder is obtained by ball milling iron-nickel-based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder under the conditions of anhydrous ethanol as the dispersion medium and argon as the protective atmosphere.

5. The production process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 4, characterized in that, The mass ratio of the iron-nickel-based alloy powder, nano-tungsten carbide, and cerium-titanium-molybdenum composite oxide powder is 60-80:10-20:

1.

6. The production process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 4, characterized in that, The ball-to-material ratio for ball milling is 6:1-8:1, and the ball milling time is 3-5 hours.

7. The production process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 5, characterized in that, The cerium-titanium-molybdenum composite oxide powder is obtained by calcining cerium-titanium-molybdenum complex dry gel in air.

8. The manufacturing process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 7, characterized in that, The calcination temperature is 500-550℃, the heating rate is 8℃ / min, and the time is 40-60min.

9. The production process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 7, characterized in that, The cerium-titanium-molybdenum complex dry gel is prepared by sol-gel method with tetrabutyl titanate ethanol solution as titanium-based main framework and cerium nitrate hexahydrate and ammonium molybdate as active coordinating metals, under the synergistic chelation of anhydrous ethanol and deionized water solvent system and acetylacetone and glacial acetic acid. The tetrabutyl titanate ethanol solution is prepared by mixing tetrabutyl titanate and anhydrous ethanol at a volume ratio of 1:

3.

10. The manufacturing process of a nano-tungsten carbide-reinforced iron-nickel-based alloy valve according to claim 9, characterized in that, The temperature of the sol-gel is 25-35℃.

Citation Information

Patent Citations

  • High-wear-resistance tungsten carbide alloy and preparation method thereof

    CN120700344A